Reconstructing livability : a grounded theory of partners' experiences of living with someone with an eating disorder - O'Connor, Patricia (Trinity College (Dublin, Ireland). School of Nursing & Midwifery, 2017)
Background: It is estimated that 200,000 people in Ireland are experiencing an eating disorder (ED). Although EDs are primarily associated with adolescents and young adults, in recent years an increase in people of older ages, many of whom are in romantic relationships, has been documented in the literature. Research into family members’ experiences of living with and supporting a person who is experiencing an ED has tended to focus on parents’ perspectives, with the perspectives of partners being seriously neglected. What knowledge is available regarding partners’ experiences is generally merged with other family members’ experiences and their unique position as a partner is rarely accounted for. Approaches to care and support for partners are primarily based on interventions developed for parents, which in the context of the intimate relationship, are often not appropriate or useful for partners. Therefore, in light of the limited knowledge available to develop appropriate and useful interventions for partners living with a person with an ED, the current research was conducted. Aim: The aim of the study was to develop a grounded theory of the personal lived experiences of intimate partners of people with an eating disorder. Methodology: The theory of ‘Reconstructing Livability’ was constructed using Classic Grounded Theory (CGT) methodology which was underpinned by a social constructionist epistemology. In-depth interviews were conducted with 18 partners of people with an eating disorder. Data were analysed using CGT principles, including concurrent data collection and analysis, theoretical sampling, constant comparative analysis and memo writing. Results: Data analysis resulted in the development of a theory conceptualised as ‘Reconstructing Livability’, where the primary concern for the participants was identified as ‘Encountering and living within a disrupted relationship’. The disruptions experienced by the participants are understood, by them, to come about as a result of their partner experiencing an ED, and as their partner experiences repeated ED setbacks, the related disruptions to the partner, the self and the relationship become increasingly evident. The theory of ‘Reconstructing Livability’ represents the cyclical process undertaken by the participants to resolve their primary concern, which in the current theory is considered a personal journey of recovery from the distress of living with the disruptions in their lives. A significant component of the participants’ recovery is that they can remain committed to their intimate relationship, despite encountering ongoing ED disruptions to it. Four stages in the cycle of ‘Reconstructing Livability’ are identified in the theory, with each stage containing various strategies undertaken by the participants as they progress towards reconstructing the livability of their relationship and a recovery of the self. The first stage ‘Encountering a disruption’, is concerned with participants becoming aware of the various aspects of their lived environment that become disrupted as a result of living with a partner with an ED to include disruptions to the partner, the self and the relationship. Once participants become aware of the disruptions they progress to the next stage of the process, ‘Informed self’. The strategies in this stage are focused on; developing a knowledge of the nature of ED, understanding what their partner may be going through and how best to support them and understanding the disruptions that have come about to their lived environment. However, becoming an ‘Informed self’ is experienced both in a distressing and a positive way but despite the distress associated with knowing, all participants acknowledge a need to improve their knowledge and understanding of EDs. The third stage in the process, ‘Countering the disruptions’ explains the strategies participants undertake to counter the disruptions to the partner, the self and the relationship. As a result of becoming an informed self, these strategies become more finely tuned with each cycle of ‘Reconstructing Livability’ they experience. As participants gain an understanding of the cyclical nature of EDs and become aware of their limitations in preventing further ED setbacks from occurring, the strategies they engage become focused on recovery of the self within the intimate relationship. This is the fourth stage of the cycle conceptualised as ‘Reclaimed livability’. A period of stability is experienced at this stage in the process until their partner experiences an ED setback, and participants re-enter the cycle again at the stage of ‘Encountering a disruption’. Conclusion: The theory of ‘Reconstructing Livability’ represents a dynamic process of personal recovery, the findings of which not only add to what is already known about the phenomenon but provides new insights into the experience of partners living with a person with an ED. The theory provides a basis on which more appropriate approaches to care and support can be developed for partners of people experiencing an ED, and offers guidance on the future direction for education of professionals, for policy development and for further research in the substantive area. Background: It is estimated that 200,000 people in Ireland are experiencing an eating disorder (ED). Although EDs are primarily associated with adolescents and young adults, in recent years an increase in people of older ages, many of whom are in romantic relationships, has been documented in the literature. Research into family members’ experiences of living with and supporting a person who is experiencing an ED has tended to focus on parents’ perspectives, with the perspectives of partners being seriously neglected. What knowledge is available regarding partners’ experiences is generally merged with other family members’ experiences and their unique position as a partner is rarely accounted for. Approaches to care and support for partners are primarily based on interventions developed for parents, which in the context of the intimate relationship, are often not appropriate or useful for partners. Therefore, in light of the limited knowledge available to develop appropriate and useful interventions for partners living with a person with an ED, the current research was conducted. Aim: The aim of the study was to develop a grounded theory of the personal lived experiences of intimate partners of people with an eating disorder. Methodology: The theory of ‘Reconstructing Livability’ was constructed using Classic Grounded Theory (CGT) methodology which was underpinned by a social constructionist epistemology. In-depth interviews were conducted with 18 partners of people with an eating disorder. Data were analysed using CGT principles, including concurrent data collection and analysis, theoretical sampling, constant comparative analysis and memo writing. Results: Data analysis resulted in the development of a theory conceptualised as ‘Reconstructing Livability’, where the primary concern for the participants was identified as ‘Encountering and living within a disrupted relationship’. The disruptions experienced by the participants are understood, by them, to come about as a result of their partner experiencing an ED, and as their partner experiences repeated ED setbacks, the related disruptions to the partner, the self and the relationship become increasingly evident. The theory of ‘Reconstructing Livability’ represents the cyclical process undertaken by the participants to resolve their primary concern, which in the current theory is considered a personal journey of recovery from the distress of living with the disruptions in their lives. A significant component of the participants’ recovery is that they can remain committed to their intimate relationship, despite encountering ongoing ED disruptions to it. Four stages in the cycle of ‘Reconstructing Livability’ are identified in the theory, with each stage containing various strategies undertaken by the participants as they progress towards reconstructing the livability of their relationship and a recovery of the self. The first stage ‘Encountering a disruption’, is concerned with participants becoming aware of the various aspects of their lived environment that become disrupted as a result of living with a partner with an ED to include disruptions to the partner, the self and the relationship. Once participants become aware of the disruptions they progress to the next stage of the process, ‘Informed self’. The strategies in this stage are focused on; developing a knowledge of the nature of ED, understanding what their partner may be going through and how best to support them and understanding the disruptions that have come about to their lived environment. However, becoming an ‘Informed self’ is experienced both in a distressing and a positive way but despite the distress associated with knowing, all participants acknowledge a need to improve their knowledge and understanding of EDs. The third stage in the process, ‘Countering the disruptions’ explains the strategies participants undertake to counter the disruptions to the partner, the self and the relationship. As a result of becoming an informed self, these strategies become more finely tuned with each cycle of ‘Reconstructing Livability’ they experience. As participants gain an understanding of the cyclical nature of EDs and become aware of their limitations in preventing further ED setbacks from occurring, the strategies they engage become focused on recovery of the self within the intimate relationship. This is the fourth stage of the cycle conceptualised as ‘Reclaimed livability’. A period of stability is experienced at this stage in the process until their partner experiences an ED setback, and participants re-enter the cycle again at the stage of ‘Encountering a disruption’. Conclusion: The theory of ‘Reconstructing Livability’ represents a dynamic process of personal recovery, the findings of which not only add to what is already known about the phenomenon but provides new insights into the experience of partners living with a person with an ED. The theory provides a basis on which more appropriate approaches to care and support can be developed for partners of people experiencing an ED, and offers guidance on the future direction for education of professionals, for policy development and for further research in the substantive area.
Keywords: Nursing and Midwifery Studies, Ph.D.; Ph.D. Trinity College Dublin